CONTENT ANALYSIS OF META ADS IN THE UMROH HOLIDAY CAMPAIGN OF ADHIYA TRAVEL - Fatona, Anindya; Ali, Dini Salmiyah Fitrah (Pena Cendekia Insani, 2026)
This study examines the construction of digital campaign messages through Meta Ads content in the Umroh Holiday campaign by Adhiya Travel amid increasing competition in the digital marketing of umrah services. The study aims to analyze how content formats, message themes, visual aesthetics, and digital performance. Using a qualitative approach, this research applies content analysis to selected Meta Ads contents (UH-1 to UH-15), complemented by digital performance data (reach, impressions, engagement, and click-through rate) and interviews with expert informants and coders for triangulation. The findings reveal that content emphasizing pilgrims’ experiences and guest star testimonials constitutes the core narrative of the campaign and achieves the highest performance in terms of engagement and visibility. Carousel and reels formats are particularly effective as they support sequential visual storytelling and emotional narratives. Visually, the campaign is characterized by bright color tones, modern typography, and the prominent presence of pilgrims and influencers, reinforcing a warm, family-oriented spiritual travel image. The study concludes that the effectiveness of Meta Ads campaigns is determined not merely by advertising exposure but by the ability of content to foster emotional connection and audience trust. These findings offer practical implications for digital umrah marketing strategies and contribute theoretically to digital marketing communication studies grounded in experiential content.